Some results for multivalued mappings in extended fuzzy b-metric spaces - Samina Batul; Faisar Mehmood; Azhar Hussain; Reny George; Muhammad Sohail Ashraf (AIMS Mathematics, 2023)
In this paper, some fixed point results for multivalued contractions are established in setting G-complete extended fuzzy b-metric spaces. An example is furnished to demonstrate the validity of results. An application of integral type inclusion is given to authenticate the theorems. Our results extend and generalize many existing results in literature.